2022
DOI: 10.1038/s41598-022-21130-6
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of IL-6 by fibroblasts exposed to Australian honeys involves lipopolysaccharide and is independent of floral source

Abstract: Honey stimulates cellular secretion of cytokines, which has been attributed to activation of lipopolysaccharide (LPS)-dependent and LPS-independent pathways. The objective of this study was to identify whether LPS is present in Australian honey samples at levels that can stimulate interleukin-6 (IL-6) secretion by fibroblasts and whether it can transduce cell signalling by activating toll-like receptor 4 (TLR4). IL-6 was measured in culture media of fibroblasts exposed to honey for 24 h. LPS was detected in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Collagen formation: With topical honey dressing, the low pH could help to create and maintain optimal conditions for fibroblasts activities, such as migration and the organization of collagen where, honey 77 and propolis 2,10 increases migration and proliferation of fibroblasts to the wound enhancing collagen types I and III expression and degradation in wounds matrix. 64 As flavonoids can promote the synthesis of collagen, 2 the fibroblasts that are responsible for the replacement of fibrin clot with scar tissue, slowing the angiogenesis and changing the collagen composition 78 resulting in favorable biochemical environment leading to re-epithelization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen formation: With topical honey dressing, the low pH could help to create and maintain optimal conditions for fibroblasts activities, such as migration and the organization of collagen where, honey 77 and propolis 2,10 increases migration and proliferation of fibroblasts to the wound enhancing collagen types I and III expression and degradation in wounds matrix. 64 As flavonoids can promote the synthesis of collagen, 2 the fibroblasts that are responsible for the replacement of fibrin clot with scar tissue, slowing the angiogenesis and changing the collagen composition 78 resulting in favorable biochemical environment leading to re-epithelization.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their role in extracellular matrix production and scar tissue formation, fibroblasts release cytokines to provide regulatory control over immune cell function. 77 Moreover, flavonoids increase vascularization and protect the vascular endothelium. 23 It was found that propolis can decrease scar formation, shorten healing time, boost wound contraction, accelerate tissue repair, and ultimately improve patients' quality of life in skin wound healing.…”
Section: Introductionmentioning
confidence: 99%